Reclaiming Rationality Experientially: The New Metaphysics of Human Spirit in Hegel’s Phenomenology (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: Hegel’s Phenomenology of Spirit is typically read as a work that either rehabilitates the metaphysical tradition or argues for a new form of idealism centred on social normativity. In the following, I show that neither approach suffices. Not only does the metaphysical reading ignore how the Phenomenology demonstrates that human rationality can never adequately capture ultimate reality because ultimate reality itself has a moment of brute facticity that resists explanation, which prevents us from taking it as a logically self-contained, self-justifying metaphysical zone traditionally known as ‘substance,’ but it also ignores how the Phenomenology equally demonstrates that human rationality creates a historically self-unfolding universe of meaning that is, because it displays a rational systematicity and consistency unlike anything else in the world, the closest thing we have to substance, but which, given its freedom, is more correctly called ‘subject.’ Consequently, while the non-metaphysical reading rightly recognizes that the Phenomenology develops a radically innovative account of intersubjectivity, it neglects how the social theory that it develops comes fully equipped with various metaphysical commitments concerning nature, spirit, and the relationship between them without which this theory would be unintelligible. KEYWORDS: Hegel, Metaphysics, Idealism, Normativity, Experience, Reason, Rationality.